2005
DOI: 10.1590/s1415-47572005000100027
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprotective effect of cysteamine against the induction of micronuclei by methyl methanesulfonate and cyclophosphamide

Abstract: Cysteamine or 2-mercaptoethylamine (MEA) is an aminothiol with a well-known radioprotective action. No specific information is available in the literature about the possible chemoprotective action of MEA against genotoxic chemical agents. This paper presents the results of studies on the ability of MEA to protect mouse bone marrow polychromatic erythrocytes against the induction of micronuclei by alkylating agents such as methyl methanesulfonate (MMS) and cyclophosphamide (CP). We observed that MEA administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Opposite to that, under alkaline conditions, including slight alkalinity (pH 11 decreased to 8) and strong (pH 12 decreased to 9), the mineral phosphate formation was slow, whereas TOC degradation rate was higher. As one can see, although the S -P bond is known to be hydrolysed under acidic and basic conditions (Santos-Mello et al, 2005), mineralisation of the byproducts is observed only under PCO conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Opposite to that, under alkaline conditions, including slight alkalinity (pH 11 decreased to 8) and strong (pH 12 decreased to 9), the mineral phosphate formation was slow, whereas TOC degradation rate was higher. As one can see, although the S -P bond is known to be hydrolysed under acidic and basic conditions (Santos-Mello et al, 2005), mineralisation of the byproducts is observed only under PCO conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Also, CPSS is known as a radioprotective substance, i.e. used for other applications (Santos-Mello et al, 2005). The objective of the research was to study the kinetics of PCO of CPSS and to follow the reaction pathway in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%